PENGETAHUAN DAN SIKAP IBU YANG MEMILIKI BALITA DALAM PEMBERIAN OBAT PENURUN PANAS DI WILAYAH KERJA PUSKESMAS BETUNGAN KOTA BENGKULU - Ningsi, Yeyen Fitri (UNIVED Press, Universitas Dehasen Bengkulu, 2018)
Fever on children is one of those cases that cannot be ignored. Based on data from a health center from January to September 2016 there were 211 febrile children with fever. One of fever treatment is to give fever-reducing medicine, which has antipyretic effect. In this case, of course knowledge and attitudes of mothers about delivering fever medications to children is very important, because of the impact that can be caused if the fever is not handled will cause brain damage, hyperpyrexia which would cause shock, epilepsy, mental retardation or learning disabilities can even endanger the safety of life.This study was to determine the relationship and attitude of mothers who have children in delivering fever medication in Betungan health center in the city.This study was an analytical study using cross-sectional design. The study population were mothers who have children with a history of fever last 3 months in Betungan health center, with the sample size of 68 people, using accidental sampling technique. Data collection was done by direct interview using a questionnaire. Data were analyzed using univariate and bivariate analysis with chi-square test at Î± 5%.The results showed that almost half of respondents (36.8%) had less knowledge about medication for fever, almost half of respondents (48.5%) had unfavorable attitude in granting febrifuge, and almost half of respondents (26.5%) whose toddlers who were not given medicine for fever. There was a relationship between knowledge of mothers who have children in drug delivery for fever in Betungan health center in Bengkulu City (Ï = 0.001), and there was a correlation between the attitudes of mothers who have children in drug delivery for fever in Betungan health center in Bengkulu City 2016 (Ï = 0.009).It is expected that Betungan health center to be more intensive to provide counseling and health promotion and provision of febrile febrifuge, such as in The Integrated Health Center, at village programs, as well as providing leaflets / brochures on granting fever medications appropriately.